Effectiveness of Educational Program on Knowledge and Practices of Nurses Regarding Prevention of Diabetic Foot Ulcers at Tertiary Care Hospital, Lahore: Knowledge and Practices of Nurses Regarding Prevention of Diabetic Foot Ulcers - Ramzan, Sonober; Sarwar, Hajra; Afzal, Muhammad; Khan, Sadia (Pakistan Journal of Health Sciences, 2022)
Diabetes is a chronic disease that affects 4.2% of the world’s population. Nurses effectively prevent foot ulcers and lower limb amputations by providing educational intervention and health care. Objective: To evaluate the effectiveness of a training program on nurses’ knowledge and practices related to diabetic foot ulcer prevention. Methods: A quasi-experimental pre-post study was conducted in the diabetes clinic and medical departments of Sir Ganga Ram Hospital in Lahore, Pakistan. A total of 36 nurses were randomly selected. After obtaining informed consent, all female nurses aged 23 to 35 years with inadequate knowledge of diabetic foot ulcer prevention were included in the study. The nurses received a 16-week intervention. Nurses’ knowledge was assessed using a validated instrument called the Nurses Knowledge Questionnaire related to Diabetic Foot Management Care and an observation checklist for nurses’ practice related to neurovascular assessment of diabetic patients before and after the intervention. Data were entered and analyzed using SPSS version 24.0. Results: The results showed that most of the participants were from 26 to 30 years, 19 (52.8) were single with educational level of nursing diploma (50.0%). Participants were having 2 to 5 years of experience. After the intervention there were 4 (11.1%), 13 (36.1%) and 19 (52.8%) participants having poor, moderate and good knowledge respectively regarding prevention of diabetic foot ulcers. There was a significant difference between pre and post interventional score of practice and knowledge among nurses (p value <0.001). Conclusions: Nurses have poor knowledge and practice regarding diabetic foot care but after the intervention it increases significantly.